Conceptualizing the foundations of a regional e-commerce strategy: Open networks or closed regimes? The case of CARICOM - Pearson A. Broome (Cogent Business & Management, 2016)
Although there has been much to boast about in advanced countries regarding e-commerce as a viable business strategy, many doubt its application to developing countries. Several papers examine individual case studies from advanced developing countries but few have presented a systemic focus on the ecosystem of an e-commerce sector, and even fewer on small island developing states (SIDS) such as the Caribbean, and those often lack a comprehensive awareness of the sector, and/or are dated. The central aim of this conceptual paper therefore is to address this lacuna by discussing the importance of understanding the broader political, social, cognitive, and economic issues and their implications and applications inherent in the development of an e-commerce sector. From this, the main objective will be to conceptualize an e-commerce strategy for their development. To realize this main aim, the article leverages a historical comparative perspective that critically examines causal analysis, experiences, and iterative processes gleaned over time from a structured analytical comparison of several national and regional case studies to conceptualize the factors and conditions under which e-commerce may contribute to, and can be adopted for development. As its main objective, the paper then presents a policy framework of recommendations guided by mutually reinforcing macro processes of change that converge at the intersection of business, policy, and information technology to inform development advocates, policy planners, and citizens within the region of what such a strategy should entail.
Keywords: 650